The Virgin Mary, monotheism, and sacrifice - Kearns, Cleo McNelly, 1943- (Cambridge ; New York : Cambridge University Press, 2008)
The Virgin Mary plays a major - although often paradoxical - role in the incarnation and crucifixion and in the ecclesiastical structure of Christianity. This role is shaped by sacrifice as understood in terms of the religious patrimony of ancient Israel and as refigured in the new Christian and Islamic paradigms arising from it. Here the offering up of a son is a frequently occurring motif, one in which fathers and mothers play an emotionally fraught, anthropologically conditioned and theologically significant role. Like such figures as Abraham and Sarah in the Hebrew Bible, Mary's relationship to sacrifice has profound implications not only for Christian theology, but for later developments in monotheism, including the role of women and gender in creating and sustaining religious identities, the emergence of competing definitions of orthodoxy, and the institution in some traditions of a masculine priesthood and religious hierarchy.
Theories of sacrifice -- Mary, motherhood and sacrifice in the Gospels -- Mary and priesthood.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Mary, -- Blessed Virgin, Saint; Mary, -- Blessed Virgin, Saint; Sacrifice -- Christianity; RELIGION -- Christian Theology -- Christology; Sacrifice -- Christianity; Electronic books